2004
DOI: 10.1016/j.theriogenology.2004.01.006
|View full text |Cite
|
Sign up to set email alerts
|

Sexual development in early- and late-maturing Bos indicus and Bos indicus × Bos taurus crossbred bulls in Brazil

Abstract: Two experiments were conducted to evaluate sexual development in early- and late-maturing Nelore (Bos indicus) and Canchim (3/8 Bos indicus x 5/8 Bos taurus crossbred) bulls and to determine predictors of sexual precocity, and pubertal and maturity status. In Experiment 1, 12 Nelore bulls where examined from 300 to 900 days of age. Puberty was characterized by an ejaculate containing > or =50 million sperm with > or =10% motile sperm, and maturity by an ejaculate containing > or =70% morphologically normal spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

10
62
1
27

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 107 publications
(100 citation statements)
references
References 35 publications
10
62
1
27
Order By: Relevance
“…The occurrence of intact sperm with a high mitochondrial membrane potential was low, probably because the experiment ended at the early maturation of the bulls, when testes were still in growth phase (Brito et al, 2004). The results suggest that the sperm of Nelore bulls only reaches full mitochondrial membrane potential at the end of sexual maturity, when the bulls become adults.…”
Section: Discussionmentioning
confidence: 82%
“…The occurrence of intact sperm with a high mitochondrial membrane potential was low, probably because the experiment ended at the early maturation of the bulls, when testes were still in growth phase (Brito et al, 2004). The results suggest that the sperm of Nelore bulls only reaches full mitochondrial membrane potential at the end of sexual maturity, when the bulls become adults.…”
Section: Discussionmentioning
confidence: 82%
“…Keys: 1= paired testes weight; 2= scrotal circumference; 3=paired epididymal weight; 4=mean epididymal length; 5=paired tunica albuginea weight; 6=mean testes volume; 7=mean testes density; 8=caput weight; 9= corpus weight; 10= cauda weight; 11= mean epididymal volume; 12= mean epididymal density; 13= mean testes length. It is particularly important to note that in the evaluation of the breeding soundness of an animal, Brito et al (2004) have reported that heavier testes produce more spermatozoa than the smaller testes. Berdston et al (1987) asserted that a testis, which possesses greater number of Sustentocytes, were heavier and produced more spermatozoa than testes with fewer Sustentocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports have shown that Nelore bulls attain puberty at ages from 14.8 to 22.1 mo. (TROCÓNIZ et al, 1991;CHASE JÚNIOR et al, 1997;BRITO et al, 2004) and such variation reflects the large genetic diversity of herds, feeding and management strategies existing in Brazil.…”
Section: Resultsmentioning
confidence: 99%